Organic structure design applications in optical and electronic devices - Chow, Tahsin J. (Pan Stanford Publishing, 2015)
The development of molecular electronics has become the mainstream of scientific research in recent decades. Applications include light-emitting diodes, solar cells, thin-film transistors, and sensors, among others. New-generation organic materials possess the virtues of softness, light weight, easy processing, design flexibility, and so on. This book focuses on the preparation of new functional organic materials. It includes a brief theoretical/kinetic discussion. The text lays special emphasis on the design of organic structures and the way they perform the designated functional properties. It will help organic chemists, particularly synthetic chemists, to light up their inspirations